Endometrial Hyperplastic Processes in Premenopause (Eurasian Medical Research Periodical, 2022)
Hormonal therapy administered for endometrial hyperplastic processes is essentially a countercurrent therapy aimed at correcting the menstrual cycle, eliminating overt estrogenic influences and preventing the formation of endometrial hyperplasia. Doctors currently have a wide range of treatments for endometrial hyperplasia in their arsenal. These include progestins, combined oral contraceptives (OCs), antigonadotropic drugs, and gonadaliberin agonists. We examined the clinical and morphological efficacy of Midiana OC for the prevention of recurrent endometrial hyperplasticity in patients with concomitant cardiovascular disease in premenopause.